Segmental and generalized vitiligo: Both forms demonstrate inflammatory histopathological features and clinical mosaicism - Venkat Ratnam Attili; Sasi Kiran Attili (Wolters Kluwer Medknow Publications, 2013)
Background: Segmental vitiligo (SV) and generalized vitiligo (GV) are perceived to evolve by different mechanisms, the former with unspecified neural mechanisms and the latter by melanocyte specific autoimmune mechanisms. However, the two diverse mechanisms are difficult to reconcile in cases of "mixed vitiligo." To test the possibility of a common pathogenesis, we reviewed clinical and histopathological features of SV and GV. Materials and Methods: As part of an ongoing histopathological study on vitiligo and vitiligo like lesions, over a 10 year period from 2002 to 2011, biopsies were taken routinely from evolving or recently evolved lesions. 50 cases of SV with quasi-dermatomal distribution and 154 cases of GV were identified and the clinical and histopathological features were compared. Results: Mild clinical inflammation was recorded in 33 of 154 GV cases but, none among 50 SV had such features. In addition to bilateral symmetrical involvement, mirror image lesions with unusual segmentation were observed in nine cases of GV. SV with a few bilateral lesions (4) and GV with quasi-dermatomal lesions (3), i.e., mixed vitiligo, were included in their corresponding groups for analytical purposes. Focal lichenoid inflammation of varying degrees around epidermal/adnexal melanocytes was identified as a common feature in evolving lesions of both SV (78%) and GV (70%). Conclusions: SV and GV demonstrated a similar inflammatory histopathological spectrum. "Segmentation/mosaicism," identified for the first time in GV is another unifying factor. Cutaneous mosaicism harboring fragile melanocyte populations, which are susceptible to external as well as auto-inflammatory mechanisms, is an attractive hypothesis to pursue in the causation of vitiligo.